2009
DOI: 10.1071/rd09091
|View full text |Cite
|
Sign up to set email alerts
|

New proteins identified in epididymal fluid from the platypus (Ornithorhynchus anatinus)

Abstract: The platypus epididymal proteome is being studied because epididymal proteins are essential for male fertility in mammals and it is considered that knowledge of the epididymal proteome in an early mammal would be informative in assessing the convergence and divergence of proteins that are important in the function of the mammalian epididymis. Few of the epididymal proteins that have been identified in eutherian mammals were found in platypus caudal epididymal fluid, and the major epididymal proteins in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…However, there is considerable divergence between extreme mammalian classes such as eutherians and monotremes. For monotremes such as the platypus, the luminal protein composition in the epididymis is unique among mammals, with numerous species-specific proteins such as E-OR20 (a new lipocalin), SPARC, and PXN-FBPL (Dacheux et al 2009). …”
Section: Composition Identification and Origin Of The Luminal Epididmentioning
confidence: 99%
“…However, there is considerable divergence between extreme mammalian classes such as eutherians and monotremes. For monotremes such as the platypus, the luminal protein composition in the epididymis is unique among mammals, with numerous species-specific proteins such as E-OR20 (a new lipocalin), SPARC, and PXN-FBPL (Dacheux et al 2009). …”
Section: Composition Identification and Origin Of The Luminal Epididmentioning
confidence: 99%
“…We have initiated such studies by analyzing micropuncture samples of luminal fluid collected along the epididymis of monotremes. Such analyses have revealed a proteomic profile of similar overall complexity to those documented from eutherians and marsupials (Dacheux et al, 2009). For instance, the resolution of platypus caudal epididymal proteins by two‐dimensional polyacrylamide gel electrophoresis (2D PAGE) resulted in the separation of at least 400 spots that could be detected by Coomassie blue staining.…”
Section: Protein Synthesis In the Monotreme Epididymismentioning
confidence: 74%
“…1-D gels of micropuncture samples of luminal fluid collected along the epididymis of the echidna (Djakiew and Jones 1983) show a similar pattern of luminal fluid proteins collected from eutherians (Dacheux et al 2003) and marsupials (Chaturapanich et al 1992a). However, whereas clusterin is the most abundant epididymal protein in the eutheria that have been studied, including humans (Dacheux et al 2003(Dacheux et al , 2006Gatti et al 2004), the most abundant secreted protein in the platypus epididymis is lipocalin (see companion paper by Dacheux et al 2009); its homologues most closely resemble proteins in the reptilian epididymis (Morel et al 2000). Of particular interest are the proteins that are secreted by the epididymis and interact with spermatozoa to modify their function.…”
Section: Division Of Labour Along the Epididymismentioning
confidence: 95%
“…Our studies of the synthesis and secretion of proteins along the monotreme epididymis (see companion paper in this issue by Dacheux et al 2009) showed that at least two new proteins are secreted into the region of the duct where spermatozoa form into bundles. In the echidna these proteins have molecular masses of ∼60 000 Da and 76 000 Da (Jones et al 2007).…”
Section: Sperm Bundlesmentioning
confidence: 98%
See 1 more Smart Citation